Women’s Political Participation - Image 2 of Respondent taken during the Field Work in Enugu - Ademola-Adeoye, Feyisayo (Locating the Albatross in Women's Political Participation in Sub-Saharan Africa, 2021)
Image on pilot study taken in Enugu, Enugu State
Keywords: Women; Sub-Saharan Africa; Political rights; Political participation; Structural Barriers; Political Barriers; Politics